2008
DOI: 10.1259/bjr/61571398
|View full text |Cite
|
Sign up to set email alerts
|

Multilocular thymic tuberculosis

Abstract: Tuberculosis is a widely prevalent disease in India. However, primary thymic involvement is an extremely uncommon presentation of this entity; a review of the literature revealed only seven documented cases of primary thymic tuberculosis. With the increasing prevalence of human immunodeficiency virus (HIV) in India, however, the occurrence of tuberculosis in previously uncommon anatomical locations may become more frequent. We report the unusual clinical, radiological and pathological findings in a HIV seroneg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Interestingly, HIV and M. tuberculosis , two of the most important pathogens in infants and young children, are both able to infect the thymus (16, 60) and thymic infection alters the output and selection of T cells in experimental models using these pathogens (9, 19). The evidence that thymic infection can compromise thymic function implies that the recruitment of protective immune responses to the thymus is essential to prevent detrimental alterations in immunological function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, HIV and M. tuberculosis , two of the most important pathogens in infants and young children, are both able to infect the thymus (16, 60) and thymic infection alters the output and selection of T cells in experimental models using these pathogens (9, 19). The evidence that thymic infection can compromise thymic function implies that the recruitment of protective immune responses to the thymus is essential to prevent detrimental alterations in immunological function.…”
Section: Discussionmentioning
confidence: 99%
“…Both in humans and animal models the thymus is itself a target of infection (719). Infection of the thymus by mycobacterial species has been reported both in humans (16) and in animal models (17–19). The incidence of thymic infection during active tuberculosis is unknown although there are several case reports in the clinical literature (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germ cell tumour, in particular seminoma and HL, should be of primary concern. Although rare, thymic tuberculosis should also be considered, which may also present as multicystic disease 172–176 …”
Section: General Remarksmentioning
confidence: 99%
“…A few recent case reports showed the thymus to be an additional site for mycobacterial dissemination (5)(6)(7)(8)(9). Using the mouse as a model, we previously showed that the thymus is a target for mycobacterial dissemination, regardless of whether the route of infection used is i.v.…”
mentioning
confidence: 99%